2023
DOI: 10.1126/sciadv.adg4417
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of enhanced lattice dynamics in a single-layered hybrid perovskite

Abstract: Layered hybrid perovskites exhibit emergent physical properties and exceptional functional performances, but the coexistence of lattice order and structural disorder severely hinders our understanding of these materials. One unsolved problem regards how the lattice dynamics are affected by the dimensional engineering of the inorganic frameworks and their interaction with the molecular moieties. Here, we address this question by using a combination of spontaneous Raman scattering, terahertz spectroscopy, and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…As n gradually diminishes from ∞ to 1, a solitary atomic layer of [PbX 6 ] 4– is isolated by the voluminous organic spacers, thus transforming the dimensionality from 3D to 2D accordingly. Owing to the soft nature, the perovskite lattices always undergo significant lattice dynamics, giving rise to octahedral tilting in and out of the perovskite planes. , For example, by measuring the mean octahedral elongation and angle variance of [PbX 6 ] 4– , Petrozza’s and Karunadasa’s groups have shown that the inorganic lattice geometries of 2D OIHPs could be deviated largely from an ideal octahedron due to the deformation of the Pb–X bond length and X–Pb–X bond angles.…”
Section: Dielectric Confinement In 2d Oihpsmentioning
confidence: 99%
“…As n gradually diminishes from ∞ to 1, a solitary atomic layer of [PbX 6 ] 4– is isolated by the voluminous organic spacers, thus transforming the dimensionality from 3D to 2D accordingly. Owing to the soft nature, the perovskite lattices always undergo significant lattice dynamics, giving rise to octahedral tilting in and out of the perovskite planes. , For example, by measuring the mean octahedral elongation and angle variance of [PbX 6 ] 4– , Petrozza’s and Karunadasa’s groups have shown that the inorganic lattice geometries of 2D OIHPs could be deviated largely from an ideal octahedron due to the deformation of the Pb–X bond length and X–Pb–X bond angles.…”
Section: Dielectric Confinement In 2d Oihpsmentioning
confidence: 99%
“…Despite its promising trajectory, this field faces many challenges. One of these is the development of sophisticated, sensitive measurement techniques capable of accurately capturing ultrafast processes under extreme conditions. Moreover, the intrinsic instability of perovskites under high-pressure conditions presents a major obstacle, complicating experimental methodologies and the interpretation of the resultant data. Ensuring structural integrity during the pressure application and dynamic measurements is imperative for reliable data acquisition and analysis.…”
mentioning
confidence: 99%